An MRI investigation of the effects of user anatomy and wheelchair cushion type on tissue deformation. Issue 1 (February 2018) - Brienza, David; Vallely, Jaxon; Karg, Patricia; Akins, Jonathan; Gefen, Amit
Abstract: Aim of the study: Tissue deformation is recognized as an important risk factor for pressure injuries. This study investigated the effects of anatomy and wheelchair cushion type on tissue deformation. Materials and methods: Direct 3-dimensional tissue deformation response was measured for six participants sitting on six different wheelchair cushions using MR imaging. Two participants had a traumatic spinal cord injury (SCI) within one year of the assessment, two sustained traumatic SCI at least 13 years prior, and two were without SCI. Tissue deformation was quantified using the difference in volume of tissue beneath the ischial tuberosity (IT) between unloaded and loaded (sitting) conditions. Results: The participants with SCI tended to have less muscle tissue volume beneath their ITs while sitting compared to participants without SCI. Reductions in muscle and fat volumes in the loaded conditions varied depending on both cushion and participant. Higher interface pressures tended to be associated with lower unloaded tissue thicknesses. Conclusion: The study showed no single cushion type tested produced the lowest amount of tissue deformation across all participants. Individual anatomy and cushion type affect deformation response of tissue and related pressure injury risk. Highlights: 3D analysis showed buttocks tissue deformation depends on the seat cushion used. No single cushion tested produced the least deformation for all participants. Anatomy and material/structure effect deformation and related pressure injury risk.